Combined General Anesthesia with Epidural Analgesia as a Modality for Adrenal Teratoma Resection in Patients with Coronary Arterial Disease - Anthony, Wibowo Kartiko,; Tjokorda G.A Senapathi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Adrenalectomy in patients with coronary arterial disease poses a significant challenge requiring good preoperative evaluation, perioperative hemodynamic control, and a detailed and careful anesthetic strategy. Teratomas are benign tumors that develop from pluripotent cells with two or more germ cell layers. Teratomas can develop in the ovaries and testes. Retroperitoneal teratoma, particularly adrenal teratoma, is rare. Indications for adrenal gland surgery include hormonal secretory tumors and non-hormonal secretory tumors. Case presentation: A 66-year-old man complained of discomfort in the right upper abdomen. From the results of the CT scan, an adrenal teratoma was obtained, and an adrenalectomy operation was planned. The patient underwent adrenalectomy with general anesthesia. Induction was carried out with propofol titrating doses of 100-150 mg until the patient was hypnotized and intubated with Atracurium 30 mg IV. The patient underwent an arterial line and CVC with ultrasound guiding during surgery. Conclusion: Anesthetic techniques should aim to maintain a myocardial oxygen supply that is greater than required to avoid ischemia. It is necessary to control perioperative hypertension, hyperglycemia, hypokalemia, and blood cortisol levels and maintain the balance of myocardial oxygen supply.